Exercise can restore behavioural and molecular changes of intergenerational morphine effects. (21st December 2021) - Sadat‐Shirazi, Mitra‐Sadat; Nouri Zadeh‐Tehrani, Setareh; Akbarabadi, Ardeshir; Mokri, Azarakhsh; Taleb Zadeh Kasgari, Bahar; Zarrindast, Mohammad‐Reza
Abstract: In our previous studies, the offspring of morphine‐exposed parents (MEO) showed pharmacological tolerance to the morphine's reinforcing effect. According to the role of exercise in treatment of morphine addiction, the current study was designed to utilize exercise to improve the effect of parental morphine exposure on the morphine's reinforcing effect. Male and female rats received morphine for 10 days and were drug‐free for another 10 days. Each morphine‐exposed animal was allowed to mate either with a drug‐naïve or a morphine‐exposed rat. The offspring were divided into two groups: (1) offspring that were subjected to treadmill exercise and (2) offspring that were not subjected to exercise. The reinforcing effect of morphine was evaluated using conditioned place preference (CPP) and two‐bottle choice (TBC) tests. Levels of dopamine receptors (D1DR and D2DR), μ‐opioid receptor (MOR), and ΔFosB were evaluated in the nucleus accumbens. The MEO obtained lower preference scores in CPP and consumed morphine more than the control group in TBC. After 3 weeks of exercise, the reinforcing effect of morphine in the MEO was similar to the control. D1DR, D2DR, and MOR were increased in MEO compared with the controls before exercise. Levels of D1DR and MOR were decreased after exercise in the MEO; however, D1DR was increased in control. D2DR level did not change after exercise in MEO, but it increased in control group. Moreover, the level of ΔFosB was decreased among MEO while it was increased after exercise. In conclusion, exercise might modulate the reinforcing effect of morphine via alteration in levels of D1DR, MOR, and ΔFosB. Abstract : The levels of dopamine receptors (D1DR and D2DR) and μ‐opioid receptors (MOR) increased in the nucleus accumbens of the offspring of morphine‐exposed parents compared with the offspring of drug‐naïve parent(s). The level of ΔFosB decreased among morphine‐exposed offspring. After treadmill exercise, the levels of D1DR and MOR decreased in the morphine‐exposed offspring, while ΔFosB increased. The possible mechanisms by which exercise modulates these changes might be due to the increase of neurotrophins, endorphins, and dopamine in the brain.